Pengaruh Literasi Digital dan Disiplin Belajar Siswa Terhadap Prestasi Belajar Siswa Pada Pembelajaran Daring Masa Pandemi Covid-19 Mata Pelajaran Ekonomi Kelas X, XI dan XII IPS Madrasah Aliyah Negeri 4 Agam - Laila Salamah; Menik Kurnia Siwi (Jurnal Salingka Nagari, 2023)
The purpose of this research to see the effect of digital literacy, the effect of learning discipline, and the simultaneous effect of digital literacy and learning discipline on learning achievements of the X, XI, and XII grade IPS students at MAN 4 Agam during online learning as the result of the COVID-19 pandemic. The method used was quantitative with an ex post facto research design. The population covered 126 X, XI, and XII grade IPS students at MAN 4 Agam. The samples were measured using Slovin’s formula. Sampling was carried out using proportional random sampling, resulting in 96 samples in total. The analysis techniques were descriptive and inductive. Hypothesis tests were F and t-tests, conducted using SPSS.The result demonstrated that (1) digital literacy had no effect on student learning achievement, (2) student learning discipline had an effect on student learning achievement, and (3) digital literacy and student learning discipline had an effect on student learning achievement. Accordingly, students should augment their learning discipline by, e.g., studying on a regular basis, finishing tasks punctually, setting a study plan or schedule, and studying in a supportive place or atmosphere